Penerapan Model Pembelajaran PAKEM dalam Meningkatkan Prestasi Belajar Pendidikan Agama Islam pada Siswa Kelas VII SMP Negeri 1 Sirenja Kecamatan Sirenja Kabupaten Donggala Tahun Pelajaran 2021/2022 - Aida Aida (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The aims of this research are: (a) Want to know the increase in student learning achievement after implementing learning strategies to improve thinking skills, (b) Want to know the effect of student learning motivation after implementing the PAKEM learning model. This research uses three rounds of action research. Each round consists of four stages, namely: design, activities and observations, reflection, and revision. The target of this research is class VII students of SMP Negeri 1 Sirenja, Sirenja District, Donggala Regency, Academic Year 2021/2022. The data obtained is in the form of formative test results, observation sheets of teaching and learning activities. From the results of the analysis, it was found that student learning achievement increased from cycle I to cycle III, namely, cycle I (52.56%), cycle II (73.91%), cycle III (91.30%). The conclusion of this research is that the PAKEM learning model can have a positive influence on the learning motivation of students at VII SMP Negeri 1 Sirenja, Sirenja District, Donggala Regency for the 2021/2022 academic year, and this learning model can be used as an alternative PAI learning.